The salinity signature of the cross-shelf exchanges in the Southwestern Atlantic Ocean: Satellite observations - Guerrero, Raul Alfredo (2014)
Satellite-derived sea surface salinity (SSS) data from Aquarius and SMOS are used to study the shelf-open ocean exchanges in the western South Atlantic near 35°S. Away from the tropics, these exchanges cause the largest SSS variability throughout the South Atlantic. The data reveal a well-defined seasonal pattern of SSS during the analyzed period and of the location of the export of low-salinity shelf waters. In spring and summer, low-salinity waters over the shelf expand offshore and are transferred to the open ocean primarily southeast of the river mouth (from 36°S to 37°30′S). In contrast, in fall and winter, low-salinity waters extend along a coastal plume and the export path to the open ocean distributes along the offshore edge of the plume. The strong seasonal SSS pattern is modulated by the seasonality of the along-shelf component of the wind stress over the shelf. However, the combined analysis of SSS, satellite-derived sea surface elevation and surface velocity data suggest that the precise location of the export of shelf waters depends on offshore circulation patterns, such as the location of the Brazil Malvinas Confluence and mesoscale eddies and meanders of the Brazil Current. The satellite data indicate that in summer, mixtures of low-salinity shelf waters are swiftly driven toward the ocean interior along the axis of the Brazil/Malvinas Confluence. In winter, episodic wind reversals force the low-salinity coastal plume offshore where they mix with tropical waters within the Brazil Current and create a warmer variety of low-salinity waters in the open ocean.